2020
DOI: 10.3389/fpubh.2020.00158
|View full text |Cite
|
Sign up to set email alerts
|

eB4CAST Approach Improves Science Communication With Stakeholders in a College-Based Health Program

Abstract: Communicating scientific results with community partners is often lacking in intervention programs, thus eB4CAST was developed to facilitate impact sharing. This article investigated using the eB4CAST dissemination tool to communicate impact from a campus-based obesity prevention program. Data from Get Fruved RCT university sites collected at baseline were used to generate eB4CAST reports. Experts (n = 13) and RCT sites (n = 15) were asked to provide feedback on eB4CAST reports based on appeal, understanding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(55 reference statements)
3
2
0
Order By: Relevance
“…The participants of this study found the eB4CAST report to be clear and easy to understand with valuable and impactful information. The positive perceptions of the eB4CAST reports aligns with previous studies using eB4CAST [24][25][26]. To date, eB4CAST has been used in a childhood obesity intervention in five states [25] and a college health program that occurred at over 50 higher education institutions [26].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The participants of this study found the eB4CAST report to be clear and easy to understand with valuable and impactful information. The positive perceptions of the eB4CAST reports aligns with previous studies using eB4CAST [24][25][26]. To date, eB4CAST has been used in a childhood obesity intervention in five states [25] and a college health program that occurred at over 50 higher education institutions [26].…”
Section: Discussionsupporting
confidence: 80%
“…The positive perceptions of the eB4CAST reports aligns with previous studies using eB4CAST [24][25][26]. To date, eB4CAST has been used in a childhood obesity intervention in five states [25] and a college health program that occurred at over 50 higher education institutions [26]. Within both of these programs, the eB4CAST approach was favorable among participants, who found the reports to be a feasible means for sharing and disseminating findings back to stakeholders [25,26].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Direct data was collected as part of the GetFruved RCT and shared with eB4CAST researchers to create the infographic report. Direct data included the Health Campus Environmental Audit (HCEA) that evaluated campus policy, dining, and recreation [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], the College Environmental Perceptions Survey (CEPS) that determined student and administrator perceptions of the healthfulness of their campus [ 32 ], Student and Administrator’s Readiness to Change which evaluated how ready the campus is to make behavioral and environmental change [ 24 ], Student and Administrator’s Priorities that examined the top five priorities for change on campus [ 24 ], and a Wellness Report card which evaluated campus physical activity, fruit, and vegetable consumption, sleep, and stress compared to national average [ 23 , 24 ]. Following the intervention, pre and post data were shown on the eB4CAST report for all scales to show change made through the GetFruved intervention.…”
Section: Tool Outcomesmentioning
confidence: 99%